2017
DOI: 10.1126/science.aan6747
|View full text |Cite
|
Sign up to set email alerts
|

Thirst-associated preoptic neurons encode an aversive motivational drive

Abstract: Water deprivation produces a drive to seek and consume water. How neural activity creates this motivation remains poorly understood. We used activity-dependent genetic labeling to characterize neurons activated by water deprivation in the hypothalamic median preoptic nucleus (MnPO). Single-cell transcriptional profiling revealed that dehydration-activated MnPO neurons consist of a single excitatory cell type. After optogenetic activation of these neurons, mice drank water and performed an operant lever-pressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
256
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 272 publications
(272 citation statements)
references
References 51 publications
9
256
0
Order By: Relevance
“…In our analysis, MnPO nNOS neurons project to various areas including the hypothalamus and the midbrain (Extended Data Fig. 9a; see also ref. 18).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In our analysis, MnPO nNOS neurons project to various areas including the hypothalamus and the midbrain (Extended Data Fig. 9a; see also ref. 18).…”
Section: Discussionmentioning
confidence: 91%
“…It has been shown that water intake rapidly suppresses the activity of thirst neurons in the lamina terminalis 10,18 (Extended Data Fig. 4).…”
Section: Mnpoglp1r → Sfonnos Inhibitory Inputmentioning
confidence: 94%
“…The activity of glutamatergic hypothalamic thirst-related neurons establishes a persistent, aversive motivational drive that animals can reduce in real time by consuming water (19, 20). The brainwide activity mode we identify appears to represent the direct effects of this thirst neuron activity that is broadcast to downstream circuits.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Although ablation of the subfornical organ did not impair drinking responses to systemic infusion of hypertonic saline in rats and sheep, 7,29 if it was ablated together with the OVLT in sheep, drinking to this stimulus was impaired compared to animals in which the OVLT alone was ablated. [36][37][38][39] Furthermore, recent experiments in mice show that optogenetic stimulation of osmoresponsive neurones in the subfornical organ or OVLT (as indicated by their expression of c-Fos in response to hypertonicity or dehydration), immediately begin to drink water. These neurones express several genes that include neuronal nitric oxide synthase (nNOS), Ca/calmodulin-dependent protein kinase II, the transcription factor ETS translocation variant-1 and the angiotensin AT 1a receptor.…”
Section: Osmoregulatory Thirstmentioning
confidence: 99%